2016
DOI: 10.1103/physreva.93.063855
|View full text |Cite
|
Sign up to set email alerts
|

Coherently coupling distinct spin ensembles through a high-Tcsuperconducting resonator

Abstract: The problem of coupling multiple spin ensembles through cavity photons is revisited by using PyBTM organic radicals and a high-Tc superconducting coplanar resonator. An exceptionally strong coupling is obtained and up to three spin ensembles are simultaneously coupled. The ensembles are made physically distinguishable by chemically varying the g factor and by exploiting the inhomogeneities of the applied magnetic field. The coherent mixing of the spin and field modes is demonstrated by the observed multiple an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 30 publications
(50 reference statements)
1
46
0
Order By: Relevance
“…2e,f and g), where only a single peak is visible at resonance. The presence of two anti-crossed branches is the experimental fingerprint of the high cooperativity regime 10,11,13,39,40 . Reproducibility of this behaviour was tested on a different sample and found in similar experimental conditions (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2e,f and g), where only a single peak is visible at resonance. The presence of two anti-crossed branches is the experimental fingerprint of the high cooperativity regime 10,11,13,39,40 . Reproducibility of this behaviour was tested on a different sample and found in similar experimental conditions (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, concentrated spin ensembles of organic radicals have been efficiently coupled to planar resonators by exploiting the exchange narrowing of their ESR lines 31,38–40 . Diluted ensembles potentially show longer coherence times but the conditions for reaching the strong coupling regime with these samples still need to be found.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting circuits are normally used as a bus to transfer quantum information between different quantum memories and registers. In a recent experiment, we have demonstrated that we can couple two or more distinguished spin ensembles through resonant microwaves photons by spectroscopic measurements [62]. Next steps along this line could be the integration of molecular spins in more complex superconducting circuits with the encoding of sequences of MW pulses.…”
Section: Molecular Spins In Hybrid Quantum Architecturesmentioning
confidence: 99%
“…The high coperativity regime was achieved by using coplanar superconducting resonators and NV centers [59] or Er spin impurities in inorganic matrix [60] at mK temperature. We are currently using high T c superconducting planar resonators [61] that show excellent performances at finite temperature (up to 50 K, at least) and in strong magnetic fields and, with these, we can achieve a strong coupling regime with 2,2-diphenyl-1-picrylhydrazyl (DPPH) [59] and (3,5-Dichloro-4-pyridyl)bis(2,4,6-trichlorophenyl)methyl (PyBTM) [62] organic radicals at the temperature of liquid helium, and even above. It is worth noting that, in these latter cases, the strong coupling regime was obtained by using concentrate samples that present sharp resonance lines due to exchange narrowing.…”
Section: Molecular Spins In Hybrid Quantum Architecturesmentioning
confidence: 99%
See 1 more Smart Citation